The perception of learning in Brazilian graduate education during the Covid-19 pandemic - Martins, Tiago André Portela (2022)
With the emergence of the COVID-19 pandemic, teaching and learning activities, as well as postgraduate learning environments, underwent changes. The main one was the transfer of classroom teaching to remote format classes, an action that was not accompanied by a consistent reflection on how this reflects on students' learning. Thus, the aim of the study was to analyze the perception of graduate students regarding learning as a result of the learning environments experienced during the social distancing resulting from the COVID-19 pandemic. The research adopted a quantitative approach of descriptive nature, having been carried out through a survey with 734 stricto sensu postgraduate students from several courses nationwide, during February 2021. The questionnaire addressed 21 variables that agglutinated in four environments of learning: physical; psychosocial; pedagogical; and technological. Through cluster analysis, five distinct groups were identified: students with high levels of learning and good use of learning environments; students with an average level of learning; students with a good level of learning and difficulties in the physical environment; students with a low level of learning; and students with learning difficulties and low use of learning environments. The results showed that a large number of graduate students in Brazil managed to adapt well in the face of the pandemic scenario and to learn satisfactorily.